The History of Cardiopulmonary Resuscitation and Where We Are Today - Maren Downing; Eren Sakarcan; Kristen Quinn (Hearts)
Cardiac arrest remains a leading cause of death worldwide and is a global health crisis. First described in the medical literature in the 18th century, modern cardiopulmonary resuscitation (CPR) with closed chest compressions has remained the standard of care since 1960. Despite exponential advances in basic science research and technological innovations, cardiac arrest survival remains a dismal 10%. The standard of care closed chest compressions provide only 20–30% of baseline cardiac output to the body. Have modern therapies plateaued in effectiveness? This article reviews the history of cardiac arrest, its therapies, and opportunities for future treatments. Through an exploration into the history of CPR and breakthroughs in its treatment paradigms, modern-day researchers and providers may find further inspiration to combat the cardiac arrest public health crisis.